Bentuk Kepala Kerbau Sebagai Ide Dalam Penciptaan Kriya Seni Ukir Kayu - Afli Afli; Irwan Irwan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The creation of this final work aims to realize a rich inspired by the shape of the buffalo head which is made as a decorative lamp, and to make a work that characterizes minangkabau that can represent the work is a typical minangkabau work and in addition with minangkabau ornamentation that adds to the aesthetic value of the work. The method applied in the creation of this final work is to use the art consortium method through five stages of work, namely (1). preparation, (2). elaboration, (3). synthesis, (4). concept realization, (5). completion. The results of the discussion are related to the beauty value of the buffalo head shape, as a symbol of the Minangkabau people. The work that the author makes is an ornamental lamp by taking the shape of a pattern from a buffalo head, and giving additional ornaments to add to the aesthetic value of the work. So that seven works are realized which are titled: